Penggunaan Mikro Irradiasi Sinar Gamma untuk Meningkatkan Keragaman Genetik pada Varietas Kedelai Argomulyo [Glycine max (L) Merr] - Hanafiah, Diana Sofia; Trikoesoemaningtyas, Trikoesoemaningtyas; Yahya, Sudirman; Wirnas, Desta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
This research used gamma ray irradiation on low doses (micro mutation). The aim of this research was to know the respons of doses level bymicro mutation on gamma ray irridation to the growing and development of Argomulyo variety of Glycine max (L) Merr (M1), the seeds isirradiated by gamma ray by micro mutation was 0 Gy, 50 Gy, 100 Gy, 150 Gy, and 200 Gy. Variation that obtained of each characters atgeneration M1 and M2 influences plants growth and development either through qualitative and quantitative that finally will influence plantsproduction. The average highest genetic variation at M 2 generation of soybean was on 200 Gy doses. Results of the research indicated thatgamma ray irradiation on 200 Gy doses was effective caused of plant variation genetic.